P31 Pseudomonas resistance with antipseudomonal monotherapy in a respiratory outpatient antibiotic therapy (respOPAT) service. (December 2018) - Lam, KKY; Bedford, L; Mayhew, A; Porter, T; Mendes, F; Sander, CR
Abstract : Introduction and objectives: Respiratory Outpatient Antibiotic Therapy (RespOPAT) has been shown to be as effective as hospital treatment with the benefit of reducing disruption to patient lifestyle. Our service is set in a teaching hospital serving both secondary and tertiary care patients. Its aims are to prevent inpatient admissions and facilitate discharges by shortening hospital admissions with patients/family members learning to self administer (40.0%) or nurses going to patient homes (60.0%). Patients using the RespOPAT service include exacerbation of bronchiectasis (51.2%) and COPD (10.4%) and empyema (11.7%). Our current protocol is to treat the majority of patients with previous Pseudomonas positive sputum with a single antipseudomonal intravenous antibiotic: Piperacillin/tazobactam, Ceftazidime or Meropenem. BTS Bronchiectasis guidelines 2010 recommend monotherapy with an antipseudomonal intravenous antibiotic, with combination antibiotics reserved for resistant strains of Pseudomonas. We aimed to evaluate whether antipseudomonal monotherapy was associated with increased rates of Pseudomonas resistance. Methods: A single-centre retrospective study of patients using the RespOPAT service between May 2015 and October 2017 was performed. Clinical information including sputum microbiology, indication for antibiotic, antibiotic administered and subsequent hospital admissions and demographic data were obtained from the electronic patient record. Results: 191 patients used the RespOPAT service for a total of 254 courses of antibiotics. 101/191 (52.9%) had a Pseudomonas positive sputum culture. Median time from first Pseudomonas positive sputum culture to RespOPAT was 158 days. 50.5% of patients cultured Pseudomonas within 30 days prior to RespOPAT. 21/191 (11.0%) cultured Pseudomonas with a single resistance to either Ciprofloxacin, Piperacillin/tazobactam, Ceftazidime or Meropenem; 7/191 (3.7%) had two or more resistances. 5/101 (5.0%) developed a post-treatment resistance to the treatment antibiotic within 3 months of receiving RespOPAT. Rates of hospital admission and those requiring further RespOPAT within 12 months will be presented for patients with and without resistant strains. Conclusions: The rate of Pseudomonas resistance is low in this population. The majority of patients do not develop resistance to treatment antibiotics. However, appropriate awareness is required to identify patients who may need combination antibiotics. A further evidence base needs to be developed to determine which patients require combination antibiotics.